Fatty acid lithium salts from Cunninghamella echinulata have cytotoxic and genotoxic effects on HL‐60 human leukemia cells. Issue 2 (9th February 2015) - Alakhras, Raghda; Bellou, Stamatia; Fotaki, Grammatiki; Stephanou, Georgia; Demopoulos, Nikos A.; Papanikolaou, Seraphim; Aggelis, George
Abstract : Polyunsaturated fatty acids, especially gamma linolenic acid (GLA), are potentially useful agents in the treatment of cancer. Cunninghamella echinulata, a fungus species that is able to synthesize GLA, when cultivated under nitrogen‐limited conditions in a medium having glucose as carbon and energy source, accumulated 32–35% of lipids containing 11–18% GLA. The conversion yield of glucose to lipid was around 0.11 g per gram of glucose consumed while the lipid production was 5 g/L. Fatty acid lithium salts (FALS) were prepared from the total Cunninghamella lipids and studied for their effects on HL‐60 human leukemic cells. Cytotoxicity of FALS on HL‐60 leukemic cells was linearly related to the FALS concentration. High FALS concentration (i.e. 15 and 20 μg/mL) induced DNA fragmentation, while concurrent treatment of cells with H2 O2 (at 100 μM) and FALS resulted in enhanced cytotoxicity of H2 O2 . However, when FALS were employed at low concentrations (i.e. 5 and 10 μg/mL), they demonstrated a protective effect on HL‐60 cells against H2 O2 genotoxicity, whereas at 20 μg/mL FALS enhanced the ability of H2 O2 to induce DNA fragmentation. It is concluded that FALS derived from C. echinulata lipids could be an effective preparation against HL‐60 human leukemic cells.